Op-ed: a new vision of sustainable communities: transforming communities and academia via the epic model - Ada Inman (1), Bryce Bray (2), Maria Inés Carabajal (3), Marshall Curry (4), Kristofer Patron-Soberano (5), Andrea Chavez Michaelsen (6) (My University, 2023)
Science and education represent the world&rsquos best opportunity to tackle global environmental challenges and to make progress toward the Sustainable Development Goals (SDGs), specifically SDG 11 (sustainable cities and communities) and SDG 17 (partnerships for the goals). We address the challenges academic institutions face for effective community engagement through education and extension initiatives and present the Educational Partnerships for Innovation in Communities Network (EPIC-N) framework as a best practice. EPIC-N represents a new paradigm on experiential learning, service learning, and partnership learning that occurs off campus with community organizations and local governments. EPIC-N operates in the US, Africa, and Asia and has started to grow larger in Latin America and the Caribbean since 2022. We argue that the co-production of knowledge methods used by EPIC-N partnerships has potential to target awareness, understanding and action to develop and implement improved strategies at the city and community level to advance SDGs in Latin America. As a disclaimer, we would like to note that all authors of this manuscript are currently, or have previously, been employed by EPIC-N.
Keywords: university-community collaboration; network; outreach; UN SDGs; co-production of knowledge; outreach; experiential learning